Messung der subjektiven Risikoeinstellung von Entscheidern: Existieren Methoden- und Personengruppenunterschiede? : are there differences between groups of methods and of persons?; Measuring the Subjective Risk Attitude of Decision-Makers: Are there Differences between Groups of Methods and of Persons? - Jor̈n Ewald; Syster Christin Maart; Oliver Mußhoff (German Journal of Agricultural Economics (GJAE), 2012)
– Many studies quantifying individual risk preferences of test persons show that results of different measuring methods may vary. Additional reservations about the reliability of the results arise from the fact that most studies are based on convenience groups, such as students or business-men in developing countries. With this in mind, we systematically compare different measuring methods to answer the question how the choice of method affects the results. Moreover, we compare the risk preferences of German farmers to those of students and Kazakhstani farmers in order to investigate whether farmers' risk preferences can be approximated through those of convenience groups. The methods applied comprise an incentive-compatible Holt and Laury lottery, as well as two psychometric methods, namely self-assessment and the selection of a business-related contextualized statement, with which the test persons are most likely to agree. Results show that the risk preferences determined by applying the aforementioned methods exhibit slightly positive but significant correlations across all three elicitation methods. Significant differences, however, only exist between the responses of students and those of German farmers, implying that it is not possible to draw conclusions from the risk attitudes of students to those of farmers. The comparison of the risk preferences of German and Kazakhstani farmers, however, reveals significant similarities with respect to the self-assessment and the business-related contextualized statements.
Keywords: 330